PENGARUH MODEL PEMBELAJARAN EXAMPLES NON EXAMPLES TERHADAP HASIL BELAJAR IPS - Paulinus Samuel, Yuli Budhiarti, (Jurnal Pembelajaran Prospektif, 2020)
When teaching using the lecture method, students are less active in learning, after taking the scores of students' Social Studies learning outcomes, no student has scored according to the standards of maximum completeness criteria. This study aims to see whether there is an effect of learning models Examples Non Examples on Social Studies learning outcomes of fourth grade students of State Elementary School 25 Perimpah. The method used in this study is the experimental method,the type of research used is quantitative and the model used is the examples non examples model. The average student learning outcomes before being given treatment (pretest) was 46 and after being given treatment (posttest) 71.33, the value of students' social studies learning outcomes increased which means there is an influence of using the learningmodel. From the results of hypothesis testing using the T test, it is obtained thtable table that is 9.714> 2.048, then Ho is rejected and Ha is accepted. The use of non examples examples learning model has an influence on students' Social Studies learning outcomes in material recognizing the types of natural resources (NR) in SDN 25 Perimpah.